Granuloma pada Limfadenitis TB: Kajian Pustaka - Aurora Rahma Koesdinar; Wida Purbaningsih; Ismet Muchtar Nur (Bandung Conference Series: Medical Science, 2022)
Abstract. Tuberculosis (TB) is an infectious infectious disease caused by Mycobacterium tuberculosis (M.tb) and is the 10th leading cause of death that ranks 4th in the world. Incidence of extrapulmonary TB events generally occurs in several organs, namely TB lymphadenitis, TB pleurisy, TB peritonitis, Miliary TB, TB meningitis, bone and joint TB. Tuberculous lymphadenitis represents about 30%–40% of cases of extrapulmonary tuberculosis. Histopathological picture TB lymphadenitis will usually be found granulomas, necrosis caseouse, epitheloid cells and Langhan's cells. Granulomas serve to isolate antigens from the host which will provide the body with protection from the introduction of antigens that are important in mycobacterial infections. Abstrak. Tuberkulosis (TB) adalah penyakit infeksi menular yang disebabkan oleh Mycobacterium Tuberculosis (M.tb) dan merupakan 10 penyebab kematian utama yang berada di urutan ke-4 di dunia. Insidensi kejadian TB ekstraparu pada umumnya terjadi pada beberapa organ yaitu Limfadenitis TB, Pleuritis TB, Peritonis TB, Miliary TB, Meningitis TB, TB tulang dan sendi. Limfadenitis TB mewakili sekitar 30%–40% dari kasus tuberkulosis ekstraparu. Gambaran histopatolgi Limfadenitis TB biasanya akan ditemukan granuloma, necrosis caseouse, epitheloid cell dan langhan’s cell. Granuloma berfungsi untuk mengisolasi antigen dari inang yang akan memberi tubuh perlindungan dari pengenalan antigen yang penting pada infeksi mikrobakteri.